1996
DOI: 10.1007/s002329900121
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Transport Heterogeneity in the Kidney: Two Independent Transporters or Different Transport Modes through an Oligomeric Protein? 1. Glucose Transport Studies

Abstract: The kinetics of Na+/d-glucose cotransport (SGLT) were reevaluated in rabbit renal brush border membrane vesicles isolated from the whole kidney cortex using a fast-sampling, rapid-filtration apparatus (FSRFA, US patent #5,330,717) for uptake measurements. Our results confirm SGLT heterogeneity in this preparation, and both high (HAG) and low (LAG) affinity glucose transport pathways can be separated over the 15-30 degrees C range of temperatures. It is further shown that: (i) Na+ is an essential activator of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…diger and Rhoads, 1994;Wright, 2001) and different properties in affinity and capacity for glucose transport between SGLT1 and SGLT2 (Turner and Moran, 1982;Oulianova and Berteloot, 1996). The present model suitably expressed the relationship between plasma glucose level and renal glucose clearance (Fig.…”
Section: Pharmacokinetic Parameters and Inhibition Constants Of Phlormentioning
confidence: 89%
See 1 more Smart Citation
“…diger and Rhoads, 1994;Wright, 2001) and different properties in affinity and capacity for glucose transport between SGLT1 and SGLT2 (Turner and Moran, 1982;Oulianova and Berteloot, 1996). The present model suitably expressed the relationship between plasma glucose level and renal glucose clearance (Fig.…”
Section: Pharmacokinetic Parameters and Inhibition Constants Of Phlormentioning
confidence: 89%
“…Two isoforms of SGLT with different affinity for glucose are localized in different positions in the proximal tubule; a low-affinity transporter (SGLT2) is expressed in the convoluted tubule, and a high-affinity transporter (SGLT1) is expressed in the straight tubule (Hediger and Rhoads, 1994;Wright, 2001). In vitro studies using renal brush-border membrane vesicles (BBMV) (Turner and Moran, 1982;Oulianova and Berteloot, 1996) indicate that the low-affinity transporter has high capacity for glucose transport and that the high-affinity one has low capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Phlorizin, an aromatic ␤-glucoside, is a well-known potent competitive inhibitor of the SGLT1 transporter (Diedrich, 1966). It is postulated that phlorizin is supposed to bind with a two-step mechanism to both the sugar-binding site of the transporter (mainly through hydrogen bonds) and to a binding site for the aglucone moiety (phloretin) mainly through hydrophobic interactions Oulianova and Berteloot, 1996;Oulianova et al, 2001). Site-directed mutagenesis studies and studies using reconstituted peptide in vitro have shown that the C-terminal loop 13 is involved in the binding of phlorizin (Novakova et al, 2001;Raja et al, 2003;Xia et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that the phlorizin binding to SGLT1 is a two-step process: rapid formation of an initial collision complex, followed by a slow isomerization process that occludes phlorizin within its receptor site (8). Phlorizin is thereby supposed to bind to both the sugar-binding site and the aglucon-binding site, the latter with a hydrophobic/aromatic surface (9,10).…”
mentioning
confidence: 99%